Phytochemicals Present in Ethanol Extract of Avocado Seed and Its Potential Antioxidant Effect - da Silva Bastos, Kaio V. L.; Souza, Adriana B.; Gomes, Rodolfo Rodrigues; de Souza, Leticia Cherpe; Aquino, Isabella Pacifico; de Moura Souza, Felipe (Current Organocatalysis, 2024)
Introduction: Pharmaceutical research currently focuses on methods that allow for more sustainable and natural approaches. In this way, the use of discarded by-products, such as avocado seed, becomes a profitable and sustainable practice. Methods: This study evaluated the extraction of phytochemicals from avocado seed (Soxhlet extraction) and compared the antioxidant capacity of avocado seed (DPPH method). The extraction found compounds of different hydrophobicity and a vast amount of compounds that may present the potential for future clinical trials. Results: Avocado extract presented an antioxidant effect (AA%) more effective than Quercetin (3.5%), Ascorbic Acid (2.8%,) and lightly lower than Rutin (-1.9%). Conclusion: Therefore, the avocado seed can be an excellent alternative for research of antioxidants and therapeutic phytochemicals.
Keywords: public health system